The 3rd International Electronic Conference on Environmental Research and Public Health—Public Health Issues in the C 2021
DOI: 10.3390/ecerph-3-09064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sensory Processing Sensitivity and Mental Health

Abstract: Sensory Processing Sensitivity, characterized by a more deeply cognitive, sensory and emotional information processing, has been previously related to several mental health problems. However, the studies are rare and an integration of the obtained findings needs to be addressed. We conducted a systematic review of studies using scientific databases in order to integrate the available information about the sensory processing sensitivity and its consequences in mental health. Thirteen studies were included and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…These were not included in the main analysis to avoid duplication in the results as they contain many of the records already identified and included in the scoping review. They are Aron et al, 2012;Castellano & Dascalu, n.d.;Costa-López et al, 2021; A flow diagram of this process is presented in Figure 1. A summary of the studies included is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…These were not included in the main analysis to avoid duplication in the results as they contain many of the records already identified and included in the scoping review. They are Aron et al, 2012;Castellano & Dascalu, n.d.;Costa-López et al, 2021; A flow diagram of this process is presented in Figure 1. A summary of the studies included is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that environmental sensitivity was directly associated with several psychological indicators of well-being [ 41 , 42 ] and functioned as a significant moderator. Specifically, with regard to the moderating role, the Vantage Sensitivity framework [ 43 , 44 ] points out that more sensitive individuals are more likely to benefit from positive environmental influences.…”
Section: Introductionmentioning
confidence: 99%
“…Entre estos numerosos estudios, un elevado número confirma la importancia de conocer y saber gestionar este rasgo desde la infancia, para evitar problemas en la edad adulta relacionados con la ansiedad, depresión, disociación y tener una vida plena y satisfactoria (Booth et al, 2015;Costa-López et al, 2021;Lionetti et al, 2021). Cuando hablamos de gestionar el rasgo nos referimos a que las PAS, al captar más información, se suelen encontrar en situaciones de sobreestimulación y sobresaturación, las cuales son difíciles de manejar, normalmente porque la persona no sabe que es Altamente Sensible.…”
Section: Introductionunclassified